PENGARUH PENGETAHUAN DEWAN TENTANG ANGGARAN DAN LATAR BELAKANG POLITIK TERHADAP PENGAWASAN KEUANGAN DAERAH: (Studi Empiris Pada DPRD Kabupaten Solok Dan DPRD Kota Solok Periode 2019-2024) - Rezi Indriani; Juita Sukraini; Siska Yulia Defitri (OPTIMAL Jurnal Ekonomi dan Manajemen, 2022)
This study aims to determine the Influence of the Council on the Budget (X1) on Regional Financial Supervision (Y), the Effect of Political Background (X2) on Regional Financial Supervision (Y), and the Simultaneous Effect of the Council's Knowledge of the Budget (X1) and Political Background. (X2) on Regional Financial Supervision (Y). The results of the study indicate that there is no effect of the Council's Knowledge of the Budget (X1) on Regional Financial Supervision (Y). The results of testing the first hypothesis are proven by the value of |t_hitung | of 0.987 < 1.682 and the significance of t is 0.330 > 0.05. After that, there is no influence of Political Background (X2) on Regional Financial Supervision (Y). The results of testing the second hypothesis are proven by the value of |t_hitung | – 0.027 < 1.682 and the significance of t is 0.978 > 0.05 of. In addition, there is no simultaneous influence of the Council's Knowledge of the Budget (X1) and Political Background (X2) on Regional Financial Supervision (Y). The results of this third test are proven by |F_hitung | 0.837 < 3.23 and a significance value of 0.440 > F of 0.05.